Pengaruh Pelatihan Kerja, Budaya Kaizen Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan PT. PLAZZA PANGESTU NUSANTARA - Nadhif, Ahnaf Kafi Aufa; Slamet, Afi Rachmat; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of job training, Kaizen culture, and leadership style on employee performance at PT. Plazza Pangestu Nusantara. This research employs a quantitative method with an explanatory approach. The sample consists of 83 employees from PT. Plazza Pangestu Nusantara. Primary and secondary data were used to support the research.The findings indicate that job training, Kaizen culture, and leadership style simultaneously affect employee performance. Partially, job training does not significantly influence employee performance. In contrast, Kaizen culture and leadership style have a significant impact on employee performance at PT. Plazza Pangestu Nusantara. Based on data analysis results using an Adjusted R Square of 0.298, it was found that job training, Kaizen culture, and leadership style contribute 29.8% to employee performance, while the remaining influence is from other variables outside the research model. Keywords: Job Training, Kaizen Culture, Leadership Style and Employee Performance